PERFECTION OF PRE-SCHOOL CHILD’S SPEECH OF DIALOGUE AND VOCABULARY DURING THE PROCESS OF GETTING ACQUAINTED WITH BOOK ILLUSTRATION - Taurina, Agrita; Vigule, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Very topical issue in many situations nowadays is caused by parent busyness, aloofness among family members, and alienation in mutual relationships; therefore, in families too little attention is devoted to many-sided development of child’s abilities, too little time is spent on direct, emotional contact in conversation. During the survey on the pre-school education and development of vocabulary carried out by 54 educators, the more and less well known topics were found out. Children are open to and interested in communication to find out how things work, developing their own vocabulary with the guidance of skilled teachers and parents. Book illustration analysis as well as the forms of conversation realization used in the research is in line with those carried out in the Project No NFI/R/2014/053 “Latvian in Monolingual and Bilingual Acquisition: tools, theories and applications”.